Which Assessment Method of Malnutrition in Head and Neck Cancer?. (June 2018) - Saroul, Nicolas; Pastourel, Rémy; Mulliez, Aurélien; Farigon, Nicolas; Dupuch, Vincent; Mom, Thierry; Boirie, Yves; Gilain, Laurent
Objective: To assess the value of several diagnostic methods of nutritional status during the initial management of a head and neck cancer. Study Design: Single-center prospective study. Setting: Tertiary referral center. Subjects and Methods: Ninety patients with head and neck cancer participated in the study. Assessment of their nutritional status was made with anthropometric, biological, body, and muscle measurements (the last by computed tomography: L3 muscle mass index [L3MMI]). Assessment of muscle performance (functional reflection of nutritional status) was made via the Short Physical Performance Battery test. The malnutrition thresholds were set according to the literature. Results: Mean body mass index (BMI) was 24.6 ± 5.4 kg/m 2 . Mean weight loss and albumin levels were –4.5 ± 10.5 kg and 37.1 ± 5.2 g/L, respectively. Fourteen percent of patients were diagnosed as malnourished on the basis of BMI, 54% according to the Nutritional Risk Index (NRI), and 58% by L3MMI. There was 64% agreement between NRI and L3MMI ( P < .001). All patients identified as malnourished by BMI were considered as such by the other assessment methods; however, many malnourished patients had normal or high BMI. The Short Physical Performance Battery score was low particularly among patients considered to be the most undernourished by the other methods. Conclusion: NRI and L3MMI are the best methods to identify patients as being malnourished. Functional muscle assessment can determine the severity of malnutrition.